Study on the Impact of Color Image and Safety Cognition on Consumers’ Car Purchasing Behavior - CHEN, CHIN-TSU; CHEN, CHUN-FU (Advances in Social Sciences Research Journal, 2018)
With the prevailing use of cars in daily life, more and more people start considering safety regarding the color of cars and accident rate. For the concern of safety, some people even attempt to treat the color of cars as a priority when buying cars. However, the color design of an automobile is more than just beauty and fashion, it is also an indicator of safe driving. This study aims to probe into the impact of the color image of cars, safety cognition, and consumers’ car purchasing behavior when purchasing a car in Taiwan. This study collects data through questionnaire survey and the SPSS statistical analysis program, and conducts t testing, one-way ANOVA, Pearson product-moment correlation analysis, and regression analysis to validate the hypotheses. According to analytical research results, car owners’ color image positively and significantly influences safety cognition; car owners’ color image positively and significantly influences consumers’ car purchasing behavior; car owners’ safety cognition positively and significantly influences consumers’ car purchasing behavior.